What Makes Tourists Go Green? An fsQCA Approach to Sustainable Behavior in Yogyakarta’s Heritage Tourism - Nur Rohman; Amin Kiswantoro; Dwiyono Rudi Susanto; Supina Supina (Universitas Pendidikan Ganesha, 2025)
Tourism’s rapid growth in Southeast Asia, particularly in heritage destinations such as Yogyakarta, Indonesia, has intensified concerns regarding environmental sustainability. Understanding why tourists engage in pro-environmental behavior remains a critical yet complex challenge for destination managers and policymakers. This study adopts a fuzzy-set Qualitative Comparative Analysis (fsQCA) to uncover configurations of psychological, situational, and contextual conditions sufficient for green behavioral intention (GBI) among domestic tourists. Drawing on the Theory of Planned Behavior (TPB), Value-Belief-Norm Theory (VBN), and Social Practice Theory (SPT), the study operationalizes five antecedent conditions: ecological attitude (ECOATT), environmental infrastructure perception (ENVINFRA), community engagement visibility (LOCALENGAGE), perceived government support (GOVTSUPPORT), and social media sustainability influence (SOCMEDINFLU). Data were collected via structured questionnaires administered to 400 domestic tourists at key heritage sites in Yogyakarta. Results reveal no single necessary condition for high GBI; instead, six distinct sufficient configurations were identified, grouped into two solution families: (i) motivational–infrastructure synergy, where strong ecological attitudes and digital social influence interact with supportive infrastructure, and (ii) compensatory governance, where policy visibility and infrastructure substitute for weak individual motivation. The overall result demonstrates strong explanatory power, with a solution consistency of 0.823, indicating that the identified configurations account for 82.3% of cases with high GBI, and a solution coverage of 0.597, capturing 59.7% of all high-GBI cases. These findings demonstrate equifinality and causal asymmetry in sustainable tourist behavior, challenging additive assumptions in traditional behavioral models. The study contributes theoretically by extending TPB and VBN frameworks with non-linear, context-sensitive pathways, integrating SPT to explain collective digital and material cues. Practically, the results provide evidence-based recommendations for infrastructure investment, social media campaigns, and policy enforcement to foster sustainability in heritage tourism destinations facing overtourism pressures.